Tingkat Pengetahuan Komunitas Green Generations terhadap Konsep Kampung Hijau dan Konservasi Air Desa Karangmanggis Boja Kendal - Irma Rohmawati; Diah Aprilia; Nadya Fitriani; Roie Megeron (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
The importance of knowledge on water conservation is indispensable to the community. Community-based education is needed because of minimal knowledge and the need to maintain human and natural balance. The lack of knowledge and awareness of the importance of water conservation efforts in Karangmanggis Boja Kendal village caused the community not to do any water conservation efforts. The purpose of this research is to analyze the knowledge level of Green Generations community of Karangmanggis Boja Kendal Village about the concept of green village and water conservation in Karangmanggis Boja Kendal Village. This research was conducted in March-April 2017 in Karangmanggis Boja Kendal Village. This research method using One Group Pretest-Postest Design method. In this design there is one group of research subjects who received treatment or treatment with workshops and materials. For further measurements are given twice before and after treatment (post test and pretest). The research subjects were 13 communities of Green Generations. The data were obtained from the pretest results given before the workshop and the provision of materials to the Green Generations and posttest communities provided after the workshop and material presentation. Data processing using descriptive qualitative analysis techniques to know the description of the data obtained. The results showed that the level of knowledge of GGs community on water conservation efforts, plants that have potential as water storage and nursery techniques increased value by 11.6% is from the average pretest value of 60.4% to 72% at posttest.